Application of Bootstrap in Building Fertilizer Inventory System Applications - Syahputra, Muhammad Zarwin; Irawan, Muhammad Dedi (Ali Institute or Research and Publication, 2022)
PT Perkebunan Nusantara II Kwala Madu plantation still uses the conventional system, especially for reports on fertilizer inputs and expenditures. So it is necessary to create a website-based application using the bootstrap framework and MySQL in order to help employees work more efficiently. The data collection technique used is by conducting observations and interviews. After doing the research, the writer implements the results of the research using a bootstrap framework and web-based MySQL which can help the work process. So that it can help employees work more accurately and efficiently.